The learning curve for hood‐sparing robotic‐assisted radical prostatectomy: A single‐surgeon experience - Keith R. S. Simpson; Jamie Krishnan; Linda Taylor; Alan McNeill; Daniel W. Good (BJUI Compass)
Abstract Objectives This study aimed to assess the impact of anterior hood‐sparing robot‐assisted radical prostatectomy (RARP) with posterior‐anterior reconstruction in a single‐surgeon series by analysing oncological and functional continence outcomes. Patients and Methods We carried out a cohort comparison study of a prospectively collected single‐surgeon series. The surgeon was an ‘in‐training’ fellowship trained surgeon in their first 2 years of independent practice. There were three cohorts identified from electronic and scanned paper operation notes. The first cohort of standard anterior RARP (no hood sparing) included initial patients and any patient in the consecutive series who had completed 3 month FU after RARP. The second cohort was hemi‐hood‐sparing RARP again within the consecutive database of patients and lastly full‐hood‐sparing RARP. Early continence was defined by patients reporting being ‘dry’ and with 0 pad or 1 confidence/security pad. Data was collected in an Excel spreadsheet, and SPSS was used to assess distribution with non‐parametric data being analysed using a Mann Whitney U test and parametric data with an unpaired t‐test. Results We identified 174 patients from March 2020 to February 2022 who were operated on. Full pathology and 6‐week follow‐up pad use data was available for all patients. At 12 months, some data for EPIC‐26 was not available (lack of response/clinic non‐attendance). The results demonstrate doubling in early continence to over 75% at 6‐week follow‐up with comparable positive margin rates. This difference was statistically significantly better in the dorsal venous complex RARP sparing group in comparison to standard RARP (p < 0.001). Conclusion Anterior hood‐sparing RARP with anterior reconstruction is a modification to the standard anterior RARP approach with a short learning curve which provides patients with better early and late continence without compromise to oncological outcomes.